2018
DOI: 10.1111/bjd.16004
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of the Janus kinase 1 inhibitor PF-04965842 in patients with moderate-to-severe psoriasis: phase II, randomized, double-blind, placebo-controlled study

Abstract: These results suggest that treatment with PF-04965842 improves symptoms and is well tolerated in patients with moderate-to-severe psoriasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 20 publications
1
64
0
1
Order By: Relevance
“…A clinical study with JAK1/2 inhibitor baricitinib, however, revealed significantly improved SLE symptoms, supporting a critical role of JAK/STAT signaling in the pathogenesis of SLE (48). As activated JAK1 elicits signals from a wide range of cytokine receptors [such as interleukin (IL)-2-, IL-4-, and IL-10-receptor families besides type I and type II IFN], specific JAK1 inhibitors are under investigation in further inflammatory skin conditions, including atopic dermatitis (AD) (49) and psoriasis (PSO) (50), which demonstrated significant beneficial effects in clinical trials, as well as hidradenitis suppurativa (NCT03569371).…”
Section: Discussionmentioning
confidence: 99%
“…A clinical study with JAK1/2 inhibitor baricitinib, however, revealed significantly improved SLE symptoms, supporting a critical role of JAK/STAT signaling in the pathogenesis of SLE (48). As activated JAK1 elicits signals from a wide range of cytokine receptors [such as interleukin (IL)-2-, IL-4-, and IL-10-receptor families besides type I and type II IFN], specific JAK1 inhibitors are under investigation in further inflammatory skin conditions, including atopic dermatitis (AD) (49) and psoriasis (PSO) (50), which demonstrated significant beneficial effects in clinical trials, as well as hidradenitis suppurativa (NCT03569371).…”
Section: Discussionmentioning
confidence: 99%
“…A clinical trial, designed to compare upadacitinib with adalimumab and placebo is ongoing (NCT02629159); all told, at least 20 clinical trials are ongoing in arthritis, IBD, and dermatological diseases (Table ). Itacitinib is also a selective JAK1 inhibitor being studied in phase 3 trials in GVHD (NCT03139604, NCT03320642) and malignancies (hematologic and solid tumor), and PF‐ 04965842 is a JAK1 inhibitor being investigated for treatment of psoriasis and atopic dermatitis . GSK2586184 is a selective JAK1 inhibitor studied in IBD, SLE, and psoriasis but a clinical trial is reported to be terminated because of drug interactions with statins (NCT02000453).…”
Section: Next‐generation Selective Jakinibsmentioning
confidence: 99%
“…inhibitor being studied in phase 3 trials in GVHD (NCT03139604, NCT03320642) and malignancies (hematologic and solid tumor), and PF-04965842 is a JAK1 inhibitor being investigated for treatment of psoriasis and atopic dermatitis. 174,175 GSK2586184 is a selective JAK1 inhibitor studied in IBD, SLE, and psoriasis but a clinical trial is reported to be terminated because of drug interactions with statins (NCT02000453).…”
Section: Jak1 Inhibitorsmentioning
confidence: 99%
“…A JAK1 inhibitor, PF-04965842, is also in clinical trials in atopic dermatis and severe psoriasis 112 . Both topical tofacitinib and ruxolitinib are tested for alopecia and vitiligo.…”
Section: Jak Inhibitor Therapiesmentioning
confidence: 99%